Anomalous point‐of‐care ketone reading following use of ethyl chloride spray as a topical anaesthetic during the treatment of a teenager with DKA. (6th December 2018) - Young, Adam; Hollowbread, Andrew; Wayman, Matthew
Abstract: We present the case of an anomalous ketone reading in a 16‐year‐old female patient with type 1 diabetes following the administration of ethyl chloride spray as a topical anaesthetic. The patient presented in diabetic ketoacidosis (DKA) and was agitated, distressed and combative. Assistance was sought in the ongoing management of the patient from the on‐call anaesthetic and intensive care team. The choice was made to use ethyl chloride spray as a topical anaesthetic. This was done in order to decrease the discomfort of capillary blood tests in an attempt to ameliorate the patient's agitation and distress. It was noted that when this spray was applied prior to point‐of‐care ketone concentration testing, a ketone reading out of context of the clinical picture was obtained. There is no caution against using ethyl chloride spray in the product literature for the ketone meter used in our hospital, but there is guidance about cleaning the hands and test site with soap and warm water. This was briefly investigated by this team and anomalous ketone concentrations were reproduced in a healthy volunteer who had ketone levels checked pre‐ and post‐application of ethyl chloride spray. There is no current published literature regarding abnormal ketone results following application of topical anaesthetic agents. Therefore, based on this experience, caution would be advised in using topical anaesthetic agents prior to capillary blood sampling and emphasis placed on strict adherence to the manufacturer's guidance of cleansing the hands and test site with warm water and soap prior to capillary sampling. Copyright © 2018 John Wiley & Sons.